1972
DOI: 10.1084/jem.136.2.241
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Antigenic Stimulation of Primary and Secondary Clonal Precursor Cells

Abstract: Cell transfers to carrier-immunized irradiated mice have permitted an analysis of the in vitro stimulation of clonal precursors of anti-2,4-dinitrophenyl (DNP) antibody-producing cells derived from both immune and nonimmune mice. The results indicate that: (a) carrier-specific enhancement is obligatory for stimulation of primary precursor cells and increases both the size and number of detectable foci derived from secondary precursors. (b) This carrier-specific enhancement is most apparent in the stimulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
231
1
1

Year Published

1973
1973
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(247 citation statements)
references
References 39 publications
14
231
1
1
Order By: Relevance
“…The methodology for in vitro B-cell cloning and the detection of positive fragment cultures by radioimmunoassay has been described previously (4,9) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The methodology for in vitro B-cell cloning and the detection of positive fragment cultures by radioimmunoassay has been described previously (4,9) .…”
Section: Methodsmentioning
confidence: 99%
“…The preparation of Limulus polyphemus hemocyanin (Hy), human gamma globulin (HyG), dinitrophenylated hemocyanin (DNP-Hy, 10 mol of DNP per 100,000 g of Hy), trinitrophenylated hemocyanin (TNP-HY, 10 mol of TNP per 100,000 g of Hy), and dinitrophenylated-human gamma globulin (DNP-HyG, 10 mol of DNP per 150,000 g of HyG) has been described previously (9) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies from this laboratory have demonstrated that the splenic focus technique permits detectable stimulation of individual neonatal or adult clonal precursor cells (28)(29)(30)(31)(32). Since tolerogens can be added to fragment cultures and removed before stimulation, this system provides a unique opportunity to compare the interaction of tolerogen with individual neonatal and adult cells.…”
mentioning
confidence: 99%
“…This constraint has recently been removed through B-cell cloning assays, in particular, the in vitro splenic focus assay developed by Klinman and Press (10,11) in which the adult splenic environment is provided complete with carrier-primed T cells, thus facilitating the measurement of B-cell precursors in fetal and neonatal tissues. It is, therefore, of great interest to combine the technique of organ culture with this sensitive B-cell cloning assay to study the differentiation of B cells in relation to immune reactivity.…”
mentioning
confidence: 99%